Doxorubicin-sensitive and -resistant colorectal cancer spheroid models: assessing tumor microenvironment features for therapeutic modulation - Valente, Ruben; Cordeiro, Sandra; Luz, André; Melo, Maria C.; Rodrigues, Catarina Roma; Baptista, Pedro V.; Fernandes, Alexandra R. (Frontiers in Cell and Developmental Biology, 2023)
The research on tumor microenvironment (TME) has recently been gaining attention due to its important role in tumor growth, progression, and response to therapy. Because of this, the development of three-dimensional cancer models that mimic the interactions in the TME and the tumor structure and complexity is of great relevance to cancer research and drug development. This study aimed to characterize colorectal cancer spheroids overtime and assess how the susceptibility or resistance to doxorubicin (Dox) or the inclusion of fibroblasts in heterotypic spheroids influence and modulate their secretory activity, namely the release of extracellular vesicles (EVs), and the response to Doxmediated chemotherapy. Different characteristics were assessed over time, namely spheroid growth, viability, presence of hypoxia, expression of hypoxia and inflammationassociated genes and proteins. Due to the importance of EVs in biomarker discovery with impact on early diagnostics, prognostics and response to treatment, proteomic profiling of the EVs released by the different 3D spheroid models was also assessed. Response to treatment was also monitored by assessing Dox internalization and its effects on the different 3D spheroid structures and on the cell viability. The results show that distinct features are affected by both Dox resistance and the presence of fibroblasts. Fibroblasts can stabilize spheroid models, through the modulation of their growth, viability, hypoxia and inflammation levels, as well as the expressions of its associated transcripts/proteins, and promotes alterations in the protein profile exhibit by EVs. Summarily, fibroblasts can increase cell-cell and cell-extracellular matrix interactions, making the heterotypic spheroids a great model to study TME and understand TME role in chemotherapies resistance. Dox resistance induction is shown to influence the internalization of Dox, especially in homotypic spheroids, and it is also shown to influence cell viability and consequently the chemoresistance of those spheroids when exposed to Dox. Taken together, these results highlight the importance of finding and characterizing different 3D models resembling more closely the in vivo interactions of tumors with their microenvironment as well as modulating drug resistance.